Analysis and framework for agricultural supply chain improvement: a case study of california papaya in cikarang - Runtuk, Johan K.; Maukar, Anstasia L. (Universitas Serang Raya, 2019)
Excessive waste is one of the problems in the food supply chain system. This study aims to identify supply chain players, map, and reduce waste that occurs in the Papaya California agribusiness supply chain process in Cikarang, Bekasi. Data collection was obtained from the results of field studies and interviews with parties involved in the supply chain such as farmers, distributors, retailers, and consumers. Increasing the effectiveness of Papaya's supply chain network is by improving the quality of packaging (modified atmosphere packaging (MAP), smart packaging, active packaging, and intelligent packaging), sharing data among chain players supply, implement refrigeration and monitor transportation technology and promote the long term. Good coordination between parties involved in the Papaya supply chain has a significant role in creating an effective and efficient supply chain system.